Peran Manajemen Pendidikan Dalam Meningkatkan Kualitas Sekolah Di Era Globalisasi - Dedi Pepriaman; Nursaimatussaddiya Nursaimatussaddiya; Tria Meisya Aziti (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
The era of globalization brings new challenges and opportunities to the world of education. Schools are required to adapt to rapid technological, information, and social changes. In this context, educational management plays a central role in ensuring school quality remains maintained and relevant to current needs. This study aims to describe the role of educational management in improving school quality in the era of globalization. The research method used is a literature review, analyzing various previous literature and research. The results indicate that educational management plays a crucial role in strategic planning, resource organization, visionary leadership, and ongoing monitoring and evaluation. The implementation of data-driven management and school digitalization are key to success in the era of globalization.